DESIGNING A NEW ENVIRONMENT AND A NEW TECHNIQUE SUBSTANTIATED WITH AUTHENTIC AND VISUAL MATERIALS IN TEACHING ENGLISH VOCABULARY TO CHILDREN WITH AUTISM - Aksoy, Kübra (PEOPLE: International Journal of Social Sciences, 2018)
Communication and learning problems occurs very early in development and serves many functions for the young autistic child. It has been implicated in the development of social, cognitive, and language skills. Processing information that is presented via the visual modality reinforces learning (Courchesne et al. 1994; Dubois & Vail, 2001). A substantial number of children with autism fail to develop these important skill and therefore experimenters with both developmental and behavior analytic perspectives have researched methods to teach with the help of visuals, videos and authentic materials in learning environment. It has been used and suggested by many research that visually presented material be used for educating children with autism (Schopler, Mesibov, & Hearsey, 1995). The purpose of this case study was to extend the analysis of typical development of social and communicative skills to the teaching of English with the help of visual, authentic materials and videos to the children with autism. Data from case study of four children with autism are provided.